Stimulus-reinforcement Based Decision-making and Anxiety: Impairment in Generalized Anxiety Disorder (GAD), but not in Generalized Social Phobia (GSP) - DeVido, Jeffrey (2008)
BACKGROUND: Generalized Social Phobia (GSP) involves the fear/avoidance of social situations while Generalized Anxiety Disorder (GAD) involves an intrusive worry about everyday life circumstances. It remains unclear whether these, highly comorbid, conditions represent distinct disorders or alternative presentations of a single underlying pathology. In this study, we examined stimulus-reinforcement based decision-making in GSP and GAD. METHODS: Twenty unmedicated patients with GSP, sixteen unmedicated patients with GAD and nineteen age, IQ, and gender matched healthy comparison individuals completed the Differential Reward/ Punishment Learning Task (DRPLT). In this task, the subject chooses between two objects associated with different levels of reward or punishment. Thus, response choice indexes not only reward/ punishment sensitivity but also sensitivity to reward/ punishment level according to between-object reinforcement distance. RESULTS: We found that patients with GAD committed a significantly greater number of errors compared to both the patients with GSP and the healthy comparison individuals. In contrast, the patients with GSP and the healthy comparison individuals did not differ in performance on this task. CONCLUSIONS: These results link GAD with an anomalous non-affective based decision-making. Further, they are indicative that GSP and GAD are associated with distinct pathophysiologies.